Response mechanisms of 3 typical plants nitrogen and phosphorus nutrient cycling to nitrogen deposition in temperate meadow grasslands - Zhang, Yang; Zhang, Qing; Yang, Wenjun; Zhang, Yan; Wang, Ning; Fan, Peixian; You, Chao; Yu, Linqian; Gao, Qun; Wang, Hui; Zheng, Peiming; Wang, Renqing (Frontiers in Plant Science, 2023)
The increase of nitrogen (N) deposition and the diversity of its components lead to significant changes in the structure and function of temperate meadow steppe, which could affect plant nutrient uptake, nutrient resorption and litter decomposition, thus affecting the biogeochemical cycle process. The distribution and metabolism of nitrogen and phosphorus in plants determine the growth process and productivity of plants. Plant nutrient uptake, nutrient resorption and litter decomposition play an important role in the nutrient cycling process of ecosystem. This study closely combined these three processes to carry out experiments with different nitrogen dosages and types, and systematically explored the response of nitrogen and phosphorus nutrient cycling to nitrogen deposition. The results showed that nitrogen deposition can greatly affect ecosystem nitrogen and phosphorus cycle. Firstly, Nitrogen deposition has significant effect on plant nutrient uptake. Nitrogen uptake of stems and leaves increased with the increase of nitrogen addition dosage, while phosphorus uptake of stems and leaves showed a downward trend or no significant effect. Besides, nitrogen addition type had a significant effect on nitrogen and phosphorus content of stems. Secondly, Nitrogen addition dosage had a significant effect on plant nutrient resorption, while nitrogen addition type had no significant effect on it. However, but the extent of the reaction was controlled by the plant species and organ types, independent of the type of N addition. Thirdly, nitrogen deposition has significant effect on litter decomposition. With the increase of nitrogen addition dosage, the initial nitrogen content of litters increased, and the decomposition rate of litters accelerated. Nitrogen application type had significant effect on stem litter decomposition. These results indicated that nitrogen enrichment significantly affects plant nutrient cycling, and thus affects the structure and function of grassland ecosystem.